(3CNdGbjGJ GdEOGQI heSDhdjI GdCYeGd aj TQcGJ GdCYeGds - (3YHhO fLe(B, (3fLes ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2022)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3CNdGbjGJ GdEOGQI(B: (3GdeaGgje h GdJWhQ, bVGjG egeI aj CNdGbjGJ GdEOGQI,GdeSDhdjI GdELJeGYjI h CNdGbjGJ GdEOGQI,CNdGbjGJ GdEOGQI aj HYV GdJLGQH GdEOGQjI,GdeSDhdjI GdHjFjI h CNdGbjGJ GdEOGQI,CNdGbjGJ GdEOGQI h CNdGbjGJ GdegfIs
(3GdeQGLY U(B.456s
Keywords: (3EOGQI GdCYeGd (B- (3CNdGbjGJ GdegfI s